Efficacy of a Chronic Care–Based Intervention on Secondary Stroke Prevention Among Vulnerable Stroke Survivors: A Randomized Controlled Trial. Issue 1 (January 2018) - Cheng, Eric M.; Cunningham, William E.; Towfighi, Amytis; Sanossian, Nerses; Bryg, Robert J.; Anderson, Thomas L.; Barry, Frances; Douglas, Susan M.; Hudson, Lillie; Ayala-Rivera, Monica; Guterman, Jeffrey J.; Gross-Schulman, Sandra; et al.
Abstract : Background: Disparities of care among stroke survivors are well documented. Effective interventions to improve recurrent stroke preventative care in vulnerable populations are lacking. Methods and Results: In a randomized controlled trial, we tested the efficacy of components of a chronic care model–based intervention versus usual care among 404 subjects having an ischemic stroke or transient ischemic attack within 90 days of enrollment and receiving care within the Los Angeles public healthcare system. Subjects had baseline systolic blood pressure (SBP) ≥120 mm Hg. The intervention included a nurse practitioner/physician assistant care manager, group clinics, self-management support, report cards, decision support, and ongoing care coordination. Outcomes were collected at 3, 8, and 12 months, analyzed as intention-to-treat, and used repeated-measures mixed-effects models. Change in SBP was the primary outcome. Low-density lipoprotein reduction, antithrombotic medication use, smoking cessation, and physical activity were secondary outcomes. Average age was 57 years; 18% were of black race; 69% were of Hispanic ethnicity. Mean baseline SBP was 150 mm Hg in both arms. SBP decreased to 17 mm Hg in the intervention arm and 14 mm Hg in the usual care arm; the between-arm difference was not significant (−3.6 mm Hg; 95% confidence interval, −9.2 to 2.2). Among secondary outcomes, the only significant difference was that persons in the intervention arm were more likely to lower their low-density lipoprotein <100 md/dL (2.0 odds ratio; 95% confidence interval, 1.1–3.5). Conclusions: This intervention did not improve SBP control beyond that attained in usual care among vulnerable stroke survivors. A community-centered component could strengthen the intervention impact. Clinical Trial Registration: URL:https://clinicaltrials.gov . Unique identifier: NCT00861081. Abstract : Supplemental Digital Content is available in the text.